1992
DOI: 10.1002/bit.260400109
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of neural networks and partial least squares for deconvoluting fluorescence spectra

Abstract: This article compares backpropagation neural networks (BNN) with partial least squares (PLS) techniques in terms of their ability to deconvolute fluorescence spectra. Both actual experimental and simulated spectral data are studied for 2 binary systems. These systems consist of mixtures of tryptophan and tyrosine, and NADH and tryptophan over a total concentration range of 10(-7) to 10(-4) M. It is shown that BNN is superior to PLS for both systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…er(x) = I(T-o)/r I (6) where T represents the target value of the parameter x and O the output estimated by the network. As an example, the relative errors can be found in Table 4 for data with and without noise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…er(x) = I(T-o)/r I (6) where T represents the target value of the parameter x and O the output estimated by the network. As an example, the relative errors can be found in Table 4 for data with and without noise.…”
Section: Resultsmentioning
confidence: 99%
“…Some workers have already reported on several applications in which neural networks have been used with success for deconvolution purposes in various fields of research [6][7][8][9], but not for calorimetric field. Furthermore, in addition to the high capability of neural networks to deal with nonlinear problems, it is known that they are highly tolerant to noise, and numerous authors have reported on very good robustness in the presence of noisy signals [10][11][12].…”
Section: New Approach Developpedmentioning
confidence: 99%
“…Specifically, in relation to biotechnological processes, several studies can be found in the literature, such as the description of the α-amilase inactivation (Geeraerd et al, 1998), the prediction of the final concentration of ethanol in a batch fermentation process (Saucedo et at., 1994) and as a soft-sensor (McAvoy et al, 1992).…”
Section: Neural Network and Hybrid Modelingmentioning
confidence: 99%
“…These effects are then recorded by the apparatus as for an experimental study and will provide a way of evaluating the transfer function, for a transformation occurring during a certain interval of time depending on its kinetic parameters, and not only applicable to a Dirac pulse or a unit step function. Some workers have already reported on several applications in which neural networks have been used with success for deconvolution purposes in various fields of research [9][10][11][12], but not for calorimetric field. Furthermore, in addition to the high capability of neural networks to deal with nonlinear problems, it is known that they are highly tolerant to noise, and numerous authors have reported on very good robustness in the presence of noisy signals [13][14][15].…”
Section: New Approach Developedmentioning
confidence: 99%
“…This occurs expecially when multiple linear regression methods for kinetic models with more than one exponent are used. Nevertheless, many comparisons have been made between artificial neural networks and conventional multivariate statistical methods [9,[16][17][18][19][20], such as multiple linear regression methods, principal components regression or partial least square regression methods, and superior results were generally obtained for neural networks.…”
Section: Network Performance Evaluationmentioning
confidence: 99%